Exploring 1,3,4-Oxadiazole Scaffold for Anti-inflammatory and Analgesic Activities: A Review of Literature From 2005-2016 - Chawla, Gita; Naaz, Baby; Siddiqui, Anees A. (Mini Reviews in Medicinal Chemistry, 2018)
1,3,4-Oxadiazole derivatives are found to have a wide range of pharmacological activities and attracting the researchers to work on this nucleus. Literature survey indicates that many 1,3,4- oxadiazoles have been synthesized with the aim to get compounds of significant anti-inflammatory and analgesic activities with reduced adverse effects. The purpose of this review is to compile the reports on 1,3,4-oxadiazole derivatives possessing anti-inflammatory and analgesic activities. The review also includes the reports on 1,3,4-oxadiazole derivatives of existing NSAIDs in the last ten years.
Keywords: COX